Respostas
respondido por:
2
MÉTODO DA SUBSTITUIÇÃO
Cálculo:
a+b=-11 >>> a=-11-b
7 (-11-b)-b=-5
-77-7-b=-5
-84-b=-5
-b=-5+84
-b=74
a=-11-(+74)
a=-11-74
a=-85
Resposta:
(-85,74)
allanrocha99:
vlwwww
respondido por:
0
Resposta:
Vou fazer pelo método de substituição:
{7a - b = - 5
{a + b = - 11
{7a - b = - 5
{b = - 11 - a
7a - (- 11 - a) = - 5
7a + 11 + a = - 5
8a + 11 = - 5
8a = - 5 - 11
8a = - 16
a = - 16/8
a = - 2
b = - 11 - (- 2)
b = - 11 + 2
b = - 9
(a , b) = (- 2 , - 9)
Verificando:
{7 • (- 2) - (- 9) = - 5
{- 2 - 9 = - 11
{- 5 = - 5
{- 11 = - 11
(a , b) = (- 2 , - 9)
Espero ter ajudado!!!
Perguntas similares
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás